A Load-Insensitive Hybrid LSK Back Telemetry System With Slope-Based Demodulation for Inductively Powered Biomedical Devices - Lee, Hyun-Su; Ahn, Jisan; Kang, Minil; Lee, Hyung-Min (IEEE transactions on biomedical circuits and systems, 2022)
This paper presents a hybrid load-shift keying (LSK) modulation for a load-insensitive back telemetry system to realize near-constant voltage changes in a primary coil ( L 1 ) against a wide range of load variations. The hybrid-LSK-enabled full-wave rectifier enables the sequential combination of open- and short-coil functions for hybrid-LSK modulation in addition to wireless power conversion operation. Load-insensitive L 1 voltage changes can be demodulated using the proposed slope- based demodulator, which utilizes the threshold slope of L 1 voltage changes over the back data pulse width, enabling robust data recovery regardless of the load conditions. The 0.56-mm 2 0.18-μm standard CMOS hybrid-LSK prototype demonstrated that the variation of L 1 voltage changes could be minimized to 60 mV under load changes between 50 Ω and 50 kΩ at coil separation distance of 10 mm, achieving 88.2% reduction compared to the conventional short-coil LSK with 510 mV variation. The proposed back telemetry system also achieved a bit error rate (BER) of < 9.1 × 10 −10 under load ranges from 50 Ω to 50 kΩ and data rate of 1 Mbps, ensuring reliable back data recovery against load variations.